Consideration Analysis of Muslim Purchase Intention on Korean Beauty Products - Moh Farid Najib; Nurul Anisa Setiani; Fatya Alty Amalia; Dewi Purnamasari (Journal of Marketing Innovation (JMI), 2022)
The purpose of this study is to analyze the considerations of Muslim consumers in buying Korean beauty products or commonly called Korean Beauty. The author also examines the effect of halal awareness, country of origin, and product ingredients on purchase intention. This research was conducted using mixed methods. The sample was obtained from primary data by distributing online questionnaires with 330 respondents and conducting in-depth interviews with four informants from West Java. For the data analysis, it employs IBM SPSS Statistics 22 for the quantitative data testing. Meanwhile, the qualitative data uses three qualitative paths: data reduction, data presentation, and conclusion. The results shows that product ingredients and country of origin have positive effects on purchase intention while halal awareness does not affect the purchase intention of Korean beauty products. These results have implications for the need of complete information in choosing products from non-Muslim countries.